Scaling up community-delivered mental health support and care: A landscape analysis - Siddiqui, Saher; Morris, Angelika; Ikeda, Daniel J.; Balsari, Satchit; Blanke, Laura; Pearsall, Miriam; Rodriguez, Roxanna; Saxena, Shekhar; Miller, Benjamin F.; Patel, Vikram; Naslund, John A. (Frontiers in Public Health, 2022)
Introduction The mental health crisis has caused widespread suffering and has been further exacerbated by the pandemic. Marginalized groups are especially affected, with many concerns rooted in social determinants. To stem this tide of suffering, consideration of approaches outside the traditional biomedical model will be necessary. Drawing from task-sharing models of mental health care that have been pioneered in low-resource settings, community-initiated care (CIC) represents a potentially promising collection of approaches. This landscape analysis seeks to identify examples of CIC that have been implemented in community settings outside of the research context in any region of the globe, in order to offer important lessons to inform scale up, while considering barriers and facilitators. Methods A narrative review approach was used for this landscape analysis where the PubMed database was searched and further supplemented with Google Scholar. Promising programs were then discussed over multiple rounds of meetings with the research team, consisting of collaborators with varying experiences and backgrounds in mental health. Using the selection criteria and feedback derived from the group meetings, a final list of programs was identified and summarized according to common characteristics and features. Results The initial PubMed search yielded 16 results, followed by screening the first 100 entries on Google Scholar. Through 5 follow-up meetings among team members, consensus was reached on a final list of 9 programs, which were grouped into three categories based on similar themes and topics: 1) approaches for the delivery of psychosocial interventions; 2) public health and integrative approaches to mental health; and 3) approaches for addressing youth mental health. Key takeaways were the importance of sustainable financing and human resources, addressing social determinants and stigma, engaging diverse stakeholders, leveraging existing health infrastructure, using sustainable training models, ensuring cultural relevance and appropriateness, and leveraging digital technologies. Discussion This landscape analysis, though not an exhaustive summary of the literature, describes promising examples of efforts to scale up community-initiated care outside of the research context. Going forward, it will be necessary to mobilize stakeholders at the community, health system, and government levels to effectively promote CIC.